2010
DOI: 10.3109/09687630802067251
|View full text |Cite
|
Sign up to set email alerts
|

‘Does anyone know where to get fits from around here?’ Policy implications for the provision of sterile injecting equipment through pharmacies in Sydney, Australia

Abstract: Background: Little is known about the factors that influence injecting drug users' (IDUs) choice of outlet, and in particular why some IDUs might prefer to use pharmacies. Greater understanding of the influences on this choice will contribute to more sophisticated policy and programme responses for blood-borne virus prevention and for health and wellbeing programmes for people who inject drugs. Method: In-depth interviews were conducted with 15 IDUs about their experiences of accessing injecting equipment from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This highlights the need to initiate strategies for increasing the coverage of OST and HCNSP in these and similar settings, which should be conducted in close consultation with service users. Evidence shows the benefits of extending opening hours and promotion of secondary distribution via peers or vending machines for increasing coverage . Additionally, better monitoring at the local district level is needed to identify lower coverage settings.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to initiate strategies for increasing the coverage of OST and HCNSP in these and similar settings, which should be conducted in close consultation with service users. Evidence shows the benefits of extending opening hours and promotion of secondary distribution via peers or vending machines for increasing coverage . Additionally, better monitoring at the local district level is needed to identify lower coverage settings.…”
Section: Discussionmentioning
confidence: 99%
“…Equally the role of policy in eliciting response from the community pharmacy sector has not been well studied, except in the area of drug misuse where, from a policy perspective, support from government, regulatory bodies and professional associations may be important catalysts to pharmacists’ participation in programmes (Myers et al , 1996). In this field at least, there are clear policy implications for service provision (Treloar et al , 2010) and supporting implementation (Chong et al , 2010). There is general commentary on policy approaches and their broad impact on the sector (Hermansyah et al , 2018; Dineen-Griffin et al , 2020) and dialogue around changes in ownership legislation and models and the impact of this on public policy (Ottewill and Magirr, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It suggests that, even in good access environments, people will use some venues over others. Other research has shown that some south‐east Sydney IDU choose pharmacies over other venues because pharmacies are commonly available, open at hours that are convenient for drug use, can be used anonymously, and there is typically less perceived police surveillance [17].…”
Section: Discussionmentioning
confidence: 99%